Features of visual disturbances in patients with newly diagnosed acromegalia (Ukrainian Journal of Ophthalmology, 2025)
Background: Acromegaly is a complex neuroendocrinologic disorder associated with hypersecretion of growth hormone (GH) and insulin-like growth factor (IGF-1) in individuals with completed physiological growth. The cause is, most commonly, an autonomously functioning pituitary adenoma (PA) secreting GH only or GH in combination with prolactin. Cuevas-Ramos and colleagues identified three structural and functional acromegaly types distinguished by clinical course, direction of tumor extension, tumor aggressiveness, expression profile of somatotroph surface receptors and potential responsiveness to treatment.Purpose: To review the features of visual disturbances in patients with newly diagnosed acromegaly.Material and Methods: We retrospectively reviewed the medical records of 174 patients with newly diagnosed acromegaly who underwent endoscopic transnasal transsphenoidal surgery for PA at the Transsphenoidal Neurosurgery Department of the Romodanov Institute during 2018 through 2011. In all patients, the diagnosis of PA was confirmed by a comprehensive morphological study. Of the 174 patients, 11.5% (20 patients; 40 eyes) had visual disturbances (reduced visual acuity and/or visual field defects) and were included in the visual disturbance group. Patients underwent clinical and neurological, endocrinological and eye examination and neuroimaging studies.Results: Visual disturbances were found preoperatively in 20 (11.5%) of the 174 consecutive patients with PA secreting GH only. Of the 20 cases, 17 (85%) were classified as type 3, and 3 (15%), as type 2 according to the structural and functional acromegaly classification of Cuevas-Ramos et al. Suprasellar extension of the pituitary adenoma towards the optic nerve-chiasm complex and compression of the crossed optic nerve fibers caused symmetric chiasmal syndrome in 11 (55%) and primary descending optic atrophy in 14 (70%) patients. After treatment, the numbers of eyes with severe and very severe visual acuity loss reduced by 5% and 7.5%, respectively, and a reduction in visual field defects was observed in 12.5% of eyes.Conclusion: We believe that the application of the structural and functional acromegaly classification by Cuevas-Ramos and colleagues would be useful not only for assessing whether a multimodal approach (comprising neurosurgery, medical therapy and radiotherapy) is required, but also for predicting the risk of developing visual disturbances in a particular case of acromegaly.
Keywords: pituitary adenoma; acromegaly; structural and functional classification; compressive optic neuropathy; endoscopic transnasal surgery